SinnRäume - An Exhibition on Contemporary Religion in Germany. Exhibition Practice as a Medium in Religious Studies SinnRäume - An Exhibition on Contemporary Religion in Germany - Celica Fitz (Journal for Religion, Film and Media, 2017)
In the research and exhibition project SinnRäume, students at the Philipps University Marburg examined the materialization of contemporary religion, exploring how religion is practiced at home, how a domestic room becomes a religious space, and how beliefs are materialized. The rooms in which religious and spiritual individuals live are often filled with objects that are attributed special meaning. Be it in a Ganesh figurine, a decorative Buddha, a simple wooden cross, or even a painted mandala hanging on the wall, the research team discovered a great variety of design elements with personal religious meaning in the private spaces they were permitted to explore. These objects have in common that their meaning is defined by not only collective but also individual criteria and by how they are integrated into everyday life. Just as the meanings of these religious objects are individual, so too are the religious lifestyles of their respective owners. The results of this project are shown in the exhibition SinnRäume - Insights into Lived Religiosity in Germany, which opened in November 2015 at the Museum of Religions (Religionskundliche Sammlung) at the Philipps University of Marburg. The exhibition concept, the presentation design, and the strategies of communication applied are an attempt to present not only religious studies research data but also the research process by which this data was acquired, as well as to relate how religious studies approaches contemporary religious culture in all its plurality.